Analisis SWOT Potensi Industri Asuransi Syari’ah Di Indoneasia : Studi Pendekatan Vivo dan Literatur Review - Rohmadi; Doni Yusuf Bagaskara (Jurnal Manajemen DIVERSIFIKASI, 2024)
This research aims to determine a SWOT analysis regarding the potential of the ShariaInsurance Industry in Indonesia using the NVivo approach. This research uses qualitativemethodology with the NVivo approach and literature review. "Data analysis techniquesinclude: (1) mapping the number of news article codes based on SWOT analysis, namely(strengths, weaknesses, opportunities and threats), regarding the "Sharia InsuranceIndustry" using NVivo 14 software; (2) map the visualization results with a hierarchicaldiagram and test the correlation between media articles using SWOT Analysis; (3) mappingresearch topics with Worldcloud or a collection of words that are often discussed in mediaarticles; and (4) Testing the significant value between media articles to determine the size orsize of the correlation around the topic "Sharia Insurance Industry". The results of thisresearch show that the topics often discussed in media articles regarding Sharia Insuranceare weaknesses and threats. Meanwhile, a topic that is rarely discussed by media articlesregarding the Sharia Insurance Industry is strengths and threats. The implications of thisresearch show that the resulting SWOT study and Literature Review providerecommendations for increasing the potential of the Sharia Insurance industry in the future.